An Efficient and Recyclable Ionic Liquid-Supported Proline Catalyzed Knoevenagel Condensation. (2011) - Zhuo, Chen; Xian, Dong; Jian-wei, Wu; Hui, Xie
Abstract : The Knoevenagel condensation reaction of aldehydes with malononitrile was described in this study, which was catalyzed by an efficient and recyclable ionic liquid-supported proline. The method represented an attractive alternative to the classical synthesis strategies and exhibited the advantage of performing homogeneous chemistry on a large scale additionally avoided large excesses of reagents. The products were obtained in good yields and reasonable purities without the need for further chromatographic purification. Moreover, the catalyst could be reused for at least four times.